Exploring the Influence Mechanism of Strategic Leadership, Employee Engagement and Job Involvement: A Framework Model Approach - Shobitha J, Shobitha J; Nagaprakash T, Nagaprakash T; Kumar, Munish; Jadhav, Aniket B. (Journal of Neonatal Surgery, 2025)
To the extent that such opportunities exist for exploring the influence mechanism between strategic leadership, employee engagement and job involvement, this research develops and validates a conceptual framework using quantitative analysis. The reason for this study is to find out whether leadership practices can affect employee attitude and behavior in organization levels. With respect to data collection, structured questionnaires were used to collect data from 300 respondents, across different industries. Results of statistical analysis including regression and correlation techniques indicated strong positive relationship including strategic leadership and employee engagement (r = 0.78, p < 0.01), job involvement (r = 0.72, p < 0.01), and job performance (r = 0.68, p < 0.01). In addition, leadership is shown to have a relationship with job involvement that is mediated by employee engagement (mediation effect = .64). This underlines the importance of transformational and ethical leaders because engagement is enhanced, and this in turn raises employee’s psychological investment in his job role. This framework model provides an excellent platform for the organizations that wish to improve strategies relevant for human resources to enable the creation of a high performance work environment. The paper contributes to the literature by demonstrating how leadership can lead to observable and actionable outcomes associated directly with employees. It also points out the significance of adopting a holistic approach to leadership, namely, motivational, trust, and autonomous leadership